Controle de Acanthoscelides obtectus com óleos essenciais de Eucalyptus spp. em grãos de feijão - Tonin, Rodrigo Jose (2015)
Brazil has been experiencing high rates of population growth and increased demand for food, but their production presents losses both quantitative and qualitative, especially the attack of pests during storage. Acanthoscelides obtectus is one of the main pests in stored beans, its control is basically done with chemical pesticides that can leave toxic residues in the grains. For this reason they are sought alternative products such as essential oils. They are a good option for this control, since it does not leave residues in food and are obtained relatively easily by farmers form. Thus, the aim of this study was to identify lead compounds and evaluate the effect of the essential oils of six species of Eucalyptus (Eucalyptus benthamii, Eucalyptus camaldulensis, Eucalyptus dunnii, Eucalyptus saligna, Eucalyptus viminalis and Eucalyptus grandis) in control of Acanthoscelides obtectus in beans. The insecticide effect for different doses and exposure times, the repellent effect and the time of persistence of the insecticide effect was evaluated. For this purpose insecticide could be observed, based on lethal dose, and the Eucalyptus saligna showed greater efficiency in mortality compared with other species. For the repellent effect it was observed that all species tested showed repellent effect on Acanthoscelides obtectus and the persistence effect the result obtained was that the insecticidal effect of the essential oils is high during the initial period losing its effect quickly.